Affective motives to play online games - Bae, Joonheui; Koo, Dong-Mo; Mattila, Pekka (Journal of global scholars of marketing science, 2016)
Most previous studies on online games have investigated the effects of cognitive motives, and thus neglected investigating affective motives. Using two studies (an experiment and a field study), the present research based on mood management theory aims to fill this void by investigating affective motives such as stress, pleasure, and arousal on intention to play online games. The present study demonstrates that the stress people experience in their life could be an initiator of online games play (Study 1), and both pleasure and arousal could be two important motives which make people stick with online games playing they have previously experienced (Study 2). We also showed that people with low self-esteem are more inclined to re-play online games when they experience more pleasure from playing games. Implications, limitations, and future research directions are discussed in conclusion.